2002
DOI: 10.1021/la0257790
|View full text |Cite
|
Sign up to set email alerts
|

In Situ, Vibrationally Resonant Sum Frequency Spectroscopy Study of the Self-Assembly of Dioctadecyl Disulfide on Gold

Abstract: We report the results of an in situ, vibrationally resonant sum frequency generation (SFG) spectroscopy study of the assembly of perdeuterated dioctadecyl disulfide on gold substrates from ethanol solutions under laminar flow conditions. The coverage evolution of the SFG spectra can be well described by the coexistence of two distinct phases: a low-coverage, disordered phase and the full-coverage crystalline phase. The structure of the adsorbed thiolate fragments in the low-coverage phase is disordered but upr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
71
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(78 citation statements)
references
References 53 publications
7
71
0
Order By: Relevance
“…Resonances near 2;220 cm −1 and 2;260 cm −1 can be assigned to asymmetric (r − ) and symmetric (r þ ) CD 3 stretching modes. Features near 2;130 cm −1 and 2;080 cm −1 are related to the CD 3 Fermi resonance (r þ FR ) and the CD stretching mode of the γ-carbon in the isopropyl group, respectively (51,52). A weak additional peak observed in the ppp spectra near 2;150 cm −1 is most likely explained by a Fermi resonance of the CD moiety (53,54).…”
Section: Methodsmentioning
confidence: 99%
“…Resonances near 2;220 cm −1 and 2;260 cm −1 can be assigned to asymmetric (r − ) and symmetric (r þ ) CD 3 stretching modes. Features near 2;130 cm −1 and 2;080 cm −1 are related to the CD 3 Fermi resonance (r þ FR ) and the CD stretching mode of the γ-carbon in the isopropyl group, respectively (51,52). A weak additional peak observed in the ppp spectra near 2;150 cm −1 is most likely explained by a Fermi resonance of the CD moiety (53,54).…”
Section: Methodsmentioning
confidence: 99%
“…6 Yang et al [25] also reported the two-step SAM formation process based on SFG measurements. They assumed that at early stage of the self-assembly process, the surface is covered with molecules in the disordered (liquid) phase and when the disordered phase density reaches a critical level, the adsorbates segregate into regions of liquid (I) and solid (II) phases in coexistence, such that the total surface coverage is the sum of the surface coverage of these two phases.…”
Section: Concentration Dependencementioning
confidence: 99%
“…Formation processes of thiol SAMs have been studied using various techniques such as electrochemistry [7], infrared (IR) spectroscopy [9][10][11], quartz crystal microbalance (QCM) [12][13][14][15], scanning tunneling microscopy (STM) [16][17][18], atomic force microscopy (AFM) [19,20], second harmonic generation spectroscopy (SHG) [21][22][23], sum frequency generation (SFG) [24,25], ellipsometry [26,27], contact angle measurement [26,27], and surface plasmon resonance (SPR) [28][29][30]. Several previous reports suggested that the SAM formation is proceeded first by rapid adsorption followed by slow reorganization [12][13][14]26].…”
Section: Introductionmentioning
confidence: 99%
“…Over the last two decades, sum frequency generation (SFG) vibrational spectroscopy has been developed into a very powerful and highly versatile spectroscopic tool for surface and interfacial studies (Anglin, 2008; Bain et al, 1995; Baldelli et al, 2008; Belkin et al, 2005; Chen, 2007; Dreesen et al, 2004; Fourkas et al, 2007; Gautam et al, 2002; Gopalakrishnan et al, 2006; Gracias et al, 1999; Holman et al, 2004; Hopkins et al, 2005; Iwahashi et al, 2008; Kim et al, 2008; Koffas et al, 2004; Li et al, 2008; Ma et al, 2006; Moore et al, 2008; Opdahl et al, 2004; Richmond, 2002; Rupprechter et al, 2008; Shen et al, 2006; Shultz et al, 2002; Stiopkin et al, 2008; Voges et al, 2007; Yang et al,2002; Ye et al, 2008). SFG is a vibrational technique that is intrinsically surface-sensitive, requires small amounts of sample, and with which the experiments can be done in situ and in real-time (Allen et al, 2000; Bain, 1995; Belkin, et al, 2005; Buck et al, 2001; Chen, 2007; Chen and Chen, 2006; Chen and Clarke, 2005; Chen and Shen, 2002; Eisenthal, 1992; Gopalakrishnan et al, 2006; Gracias et al, 1999; Hopkins, et al, 2005; Koffas et al, 2004; Lambert et al, 2005; Miranda et al, 1999; Moore et al, 2008; Opdahl et al, 2004; Perry, et al, 2006; Richmond, 2001; Richmond, 2002; Shen, 1989; Shen et al, 2006; Shultz et al, 2000; Tadjeddine et al, 1996; Wang and Gan, 2005; Williams et al, 2002; Zhuang et al, 1996).…”
Section: Introductionmentioning
confidence: 99%